The organizational structure of international drug smuggling - Benson, Jana S.; Decker, Scott H. (Journal of criminal justice, 2010)
While most group offending is not well organized, it is generally assumed that high levels of organization can be found in group offending that generates revenue, such as white-collar crime, drug sales, and smuggling drugs or humans. The organizational structure of international drug smuggling has typically been viewed as highly rational and formally structured. Employing interviews with thirty-four federal prisoners convicted of smuggling large volumes of cocaine into the United States, this study explored the organizational structure of high level international drug smuggling. The subjects described a general lack of formal structure and depicted the drug smuggling operations as composed of isolated work groups without formal connections among each other. These findings bring into question the idea that these groups are rationally organized around pursuing efficiency and support recent research that suggests network security or minimizing risk are key organizing principles of drug trading organizations.